Analisis prestasi belajar kewirausahaan ditinjau dari perhatian orang tua, media pembelajaran dan kinerja guru terhadap siswa smk negeri - Kiswati, Kiswati; Purbonuswanto, Welius; Christian, Daniel Grace (Universitas Sebelas Maret, 2021)
This study aims to determine the influence of parental attention, learning media, and teacher performance individually on the achievements of learning Entrepreneurship students of SMK Negeri Kebumen Year 2020-2021, and to know the influence of parental attention, learning media, and teacher performance together on the achievements of entrepreneurial learning students of SMK Kebumen Year 2020-2021. This research was conducted at SMK Negeri 1 Karanganyar and SMK Negeri 1 Kebumen. The research time is November 2020 to January 2021. This study uses a quantitative correlational approach with a population of 643 students. The sample was determined by 25% or as many as 160 students taken by cluster random sampling method. Data analysis includes descriptive analysis, prerequisite test analysis of data analysis, and hypothesis test. The results of this study showed that the variables of entrepreneurial learning achievement were influenced by parental attention variables by 27.3%, learning media variables by 24.8%, teacher performance variables by 18.1%, and from the three variables together by 70.2% so that there are still 29.8% other factors that can affect the achievement of entrepreneurial learning but were not studied in this study. Therefore, it is expected that in further research can be found other factors that can influence the achievement of learning entrepreneurship.